Editorial - Oniwide, Oyetola Olaoluwa (NIU Journal of Humanities, 2023)
This issue of KIU Journal of Humanities touches on Development Administration, Educational Psychology, Literary Studies, Religious Studies and Legal Studies. The first part of the Journal focues on Development Administration. One of the papers in this section reveals that that there are both natural and human causes of environmental degradation eventhough human causes are more than the natural. It is uncovered that humans have continued to exploit nature through the irresponsible use of natural resources. This paper, therefore, concludes that environmental degradation problems in Nigeria can be effectively address through Christian stewardship, eco-justice and creation spirituality, which are the emerging environmental ethical ideologies in contemporary Christianity and other Christian ecological values inherent in the bible. Nigerian Christians must become ambassadors of these environmental ethical principles for effective ecological healing in the country. Papers in section two explore issues in Educational Psychology. It is postulated in one of the papers that there is a negative or inverse   relationship between academic performance and stress, anxiety and depression, meaning that the higher the students’ level of stress, anxiety, and depression, the lower the academic performance. It is, therefore, recommended that school counsellors and psychologists should be encouraged to address the issues of stress, anxiety and depression especially among hundred level students so as to enhance their adjustment and academic performance. One of the papers, in the third section is on Language and Literary Studies, demonstrates that the spoken aspect of a language is very vital in the learning of a foreign language. The paper lays emphases on effective oral communication amongst students in a bilingual environment and in the same vein recommends some pedagogical techniques in enhancing and promoting effective oral communication in French. Papers in section four deals with issues in Religious Studies. While advocating socio-economic and religious restructuring of Nigeria based on the principle of maslaha al-mursalaha , one of the papers in this section, recommends that 1999 Constitution should be amended to accommodate laws that will address issues on resource control and restructuring. The paper further recommends that states should be allowed to take 80% of the resources found in their respective states or regions while 20% of the resources should be allocated to the Federal Government.  And the Federal Government of Nigeria should also promote justice, fairness and equity (which Islam preaches) among the federating units and continue to wage ‘war’ against corruption, insurgency, militancy, kidnapping and other crimes (which Islam forbids) that are threatening the cooperate existence of Nigeria. In the last section which centres on Legal Studies, one of the papers concludes and recommends that embracing non-custodial sentencing will reduce prison reception and minimize the enormous government resources in maintaining the prison infrastructure and the prisoners in Nigeria. In this regard, the paper suggests that there is need for a redress of the challenges mitigating the smooth application of non-custodian sentences in Nigeria's criminal Justice System. On the whole, this issue of KIU Journal of Humanities features many empirical and theoretical based articles which can be of great benefit to every reader.